A Patternless Piezoelectric Energy Harvester for Ultra Low Frequency Applications - Awal, M. R.; Jusoh, M.; Sabapathy, T.; Ahmad, R. B.; Kamarudin, M. R.; Osman, M. N.; Ahmad, M F.; Rahman, S. A.; Dagang, A. N. (International Journal of Integrated Engineering, 2020)
This paper presents a pattern less piezoelectric harvester for ultra low power energy applications. Usually patterned cantilevers are used as vibration energy harvester which results additional fabrication process. Hence, to reduce the process, a four layer cantilever configuration is used to design the harvester with Aluminum, Silicon and Zinc Oxide. The device dimension is settled to 12×10×≈0.5009 mm3 with ≈300 nm deposition thickness for each layer. The modeling and fabrication processes are demonstrated in detail. The induced voltage by the cantilever is obtained through the analytical and practical measurements. From the measurements, it is found that, the maximum induced voltage is 91.2 mV from practical measurement with voltage density of 1.517 mV/mm3. It is evident from the results that, this pattern less model can be useful for next generation vibration energy harvester with simpler technology.